Robinson’s cytological grading of breast carcinoma: it’s prognostic implications and correlation with bloom Richardson’s histological grading of breast cancer - Jivani, Toral; Bhatt, Maitri; Shukla, Ashwini; Godhani, Suchi (International Journal of Research in Medical Sciences, 2024)
Background: Cytological grading on aspirates of breast carcinoma is a useful tool for surgical maneuver and prognosis. The aim of the study is to find out the utility of grading in malignant breast tumors using Robinson’s cytological grading on FNAC and correlating it with modified bloom-Richardson’s histopathological grading of breast carcinoma along with lymph node status assessment post-operatively by histopathological examination. Methods: This prospective study was carried out in 40 cases of invasive duct carcinoma of breast for a period of one and half year duration from December-2019 to July-2021. This study was done in department of pathology, Surat municipal institute of medical education and research (SMIMER), Surat. In all these cases the cytological diagnosis was confirmed by histological examination. All cases were graded by using Robinson’s grading system. All these cases were also correlate with bloom Richardson’s grading system on histopathology in mastectomy specimen. Result: Robinson’s cytological grading correlated well with bloom Richardson’s histopathological grading. In this study of forty cases, thirty-three cases (82.5%) show concordance between cytologic and histologic grading system. Rest of the seven cases (17.5%) show discrepancy. Conclusions: Thus, In the most of the cases, cytological grading of breast carcinomas correlate with histopathological grading and may be useful as a prognostic marker. It was concluded that the cytological grading should be included in all FNAC reports. So that appropriate decision regarding the preoperative neoadjuvant chemotherapy can be made and overtreatment of low-grade cancers has been avoided.